Identifikasi Gunung Api Purba Karangtengah di Pegunungan Selatan, Wonogiri, Jawa Tengah - Abdissalam, Rus; Bronto, Sutikno; Harijoko, Agung; Hendratno, Agus (Geological Agency, 2009)
DOI:Â 10.17014/ijog.v4i4.85Karangtengah area in the southeastern part of Wonogiri Regency, is part of the Southern Mountains which is wholly composed of Tertiary volcanic rocks. Nevertheless, the eruptive centre of these volcanic rocks is still unknown. Based on an integrated study that comprises geomorphology, stratigraphy, structural geology, petrology, alteration, and mineralisation the existence of Karangtengah paleovolcano can be identified. The paleovolcano was formed below sea water, basaltic in composition, and it was part of a volcanic island arc during the time. Volcanogenic minerals are found in the central facies containing Fe, Cu, Pb, and Zn.